2017
DOI: 10.1042/cs20171069
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TrpC5 promotes tumor metastasis via the HIF-1α–Twist signaling pathway in colon cancer

Abstract: In cancer cells, intracellular Ca homeostasis is altered, and this is involved in tumor initiation, progression, and metastasis. However, little is known about the underlying mechanisms. Here, we report that transient receptor potential channel 5 (TrpC5), a receptor-activated non-selective Ca channel, is correlated with tumor metastasis in colon cancer patients. Moreover, in colon cancer cells, overexpression of TrpC5 caused a robust rise in the concentration of ([Ca]), decreased E-cadherin, and increased mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 49 publications
1
36
0
1
Order By: Relevance
“…Similar to our study, where 5-FU was administered at a dose of 5 μM for 24 hours, they reported that 5-FU showed similar effect at all stages of the molecular pathway of apoptosis by increasing intracellular (Ca 2+ ) levels through TRPV1 channel activation (42). Increased TRPC5 expression in colon cancers was reported in literature (43), although TRPM2 channels were reported to play a role in tumour proliferation in breast cancer and may be used as invasion markers and play a role as prognostic factors (15). However, our study has established for the fi rst time that TRPM2 channels had similar effects on colon cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our study, where 5-FU was administered at a dose of 5 μM for 24 hours, they reported that 5-FU showed similar effect at all stages of the molecular pathway of apoptosis by increasing intracellular (Ca 2+ ) levels through TRPV1 channel activation (42). Increased TRPC5 expression in colon cancers was reported in literature (43), although TRPM2 channels were reported to play a role in tumour proliferation in breast cancer and may be used as invasion markers and play a role as prognostic factors (15). However, our study has established for the fi rst time that TRPM2 channels had similar effects on colon cancer cells.…”
Section: Discussionsupporting
confidence: 89%
“…HIF-1α is a Ca 2+ -sensitive factor that promotes EMT by directly regulating Twist expression (Chen et al 2017). Hypoxia in the tumor followed by HIF-1α is one of the most important mechanisms to promote tumor progression and metastasis (Yang and Wu 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Except Piezo1, MCU, an evolutionarily conserved Ca 2+ channel, has been found, which plays a role in regulating intracellular Ca 2+ signaling for mitochondria (Cui et al 2017;Ren et al 2017). HIF-1α, a Ca 2+ -sensitive factor, has been confirmed to be involved in tumor cell metastasis by promoting EMT (Chen et al 2017). Although Piezo1 has been extensively studied after being confirmed as a mechanical sensor, functional research of this protein is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…This close interdependence between TRPC5 and Rac1 could suggest a positive feedback mechanism in which the Rac1-mediated TRPC5 insertion from a vesicular pool into the cell membrane leads to enhanced TRPC5-mediated Ca 2+ influx, which in turn triggers the activation of Rac1 and the subsequent migratory phenotype. Although a direct correlation between TRPC5/TRPC6 and Rac1/RhoA has not yet been established in cancer models, it is possible to speculate that a similar interplay may also occur in the regulation of cancer cells migration, taking into account the evidence for direct involvement of TRPC5 and TRPC6 in the increased migratory potential of several cell types ( Greka et al, 2003 ; Xu et al, 2006 ; Rampino et al, 2007 ), including some tumors such as colon cancer and glioblastoma ( Chigurupati et al, 2010 ; Chen L. et al 2017 ; Chen Z. et al, 2017 ). However, whether these effects on tumor migration are dependent on the impact of TRPC5 and TRPC6 activity on cell contractility and motility remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Both TRP channels and small GTPases have been implicated in increased tumor invasiveness through the induction of MMPs expression ( Betson and Braga, 2003 ; Yang and Kim, 2020 ). Indeed, TRPM2, TRPM7, TRPM8, TRPV2, and TRPC1 have shown to cause upregulation of MMP9 in a Ca 2+ -dependent manner in gastric, bladder, oral squamous, prostate and thyroid cancer cells respectively ( Monet et al, 2010 ; Okamoto et al, 2012 ; Asghar et al, 2015 ; Cao et al, 2016 ; Chen L. et al 2017 ; Chen Z. et al, 2017 ; Almasi et al, 2019 ). Additionally, TRPM2, TRPM7, and TRPC1 activity have been also correlated with MMP2 production in gastric, lung, pancreatic and thyroid cancer ( Asghar et al, 2015 ; Rybarczyk et al, 2017 ; Liu et al, 2018 ; Almasi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%